Management of Malnutrition and Obesity with Respect to Malignancy - Baskaran, R.; Rajasekaran, B. Ajay; Thangam, T. Kalai; Nithiya, B. A. M. (Research Highlights in Disease and Health Research Vol. 9, 2023)
Background: Cancer is predicted to be an increasingly important cause of mortality in the next few decades worldwide. It is challenging to find specific link between a food or nutrient and cancer. In the same way the starvation-related malnutrition and chronic disease-related malnutrition cannot be identified easily. Majority of cancer patients deaths are related to malnutrition, not the malignancy itself. Methods: The indicators like overweight and underweight are used to measure nutritional imbalance; The unintentional weight loss and a low body weight are the common signs of malnutrition. Hematological studies include a Complete Blood Count with Red Blood Cells indices, albumin, pre albumin, transferrin, platelet-to-lymphocyte ratio and a peripheral smear are used to determine the mal nutrition. Overweight patients in random of both genders have been taken in to consideration and test results have been compared. The importance of consumption of the Cruciferous vegetables which lowers the Head, neck, esophageal cancer and Stomach cancer has been highlighted in this paper. List of locally available cancer fighting fruits, vegetables and plants are given in this paper to increase the awareness of people to maintain their health. All major types of cancers are also discussed with symptoms, reason, diets and prevention methods in a easily understandable way. Results: Patients with very high BMI and Patients with poor health status with very low BMI are more chances of getting cancer. Lab tests are erratic in the case of obese people and poor health people. Males and non vegetarians are more affected with cancer compared with females and vegetarians respectively. Outcome: This article creates awareness to common people about the impacts of malnutrition and obesity so that the intensity of the disease like cancer spreading can be minimized and fatality can be prevented. The excess body fat increases the risk for several cancers, including colorectal, post-menopausal breast, uterine, esophageal, kidney and pancreatic cancers because fat tissues produce excess amounts of estrogen. People with obesity often have increased blood levels of insulin and Long-term increased insulin raises the risk for breast, prostate and colorectal cancers.